Charleston to Phnom Penh : a cook's journal - Taylor, John Martin, 1949- (University of South Carolina Press, 2022)
"A journey through the lands of boiled peanuts, pesto, and pickled peppercorns-with thirty recipes. Foodies, travel enthusiasts, culinary historians, fans of fine writing, and cookbook collectors will feast on John Martin Taylor's Charleston to Phnom Penh. A unique vision of a joyous and peripatetic life, these essays take readers on a journey across three continents, from the South Carolina Lowcountry of Taylor's upbringing to the Caribbean, Italy, France, Eastern Europe, and Asia. Taylor recalls his mother's before-her-time culinary experiments; probes historical archives to research the origins of classic dishes; and remembers adventures sailing, dancing, and fishing, as well as cooking. His gaze is social, etymological, personal, comic, and historical, and all foods are considered fair game for scrutiny. Taylor tells us how to bake with olive oil, why he doesn't make wedding cakes, what to do in Transylvania, and how he came to be a voice of the Lowcountry. Make a margarita and delve into his deconstruction of Hoppin' John, his erstwhile namesake; the history of cheese straws; and how to make callaloo and fish amok"--